Research on inter-turn short circuit fault location of SF6 circuit breaker energy storage motor coil based on traveling wave reflection method. Issue 1 (1st April 2022) - Qin, Jian; Peng, Yanjun; Wang, Lu; Wang, Jianxi; Pan, Ningbo; Huang, Yongqiang; Zhang, Xiaohui
Abstract: —The traveling wave reflection method is proposed to locate the inter-turn short circuit fault of the circuit breaker energy storage motor coil. The capacitance and inductance matrices of the energy storage motor coil are calculated by finite element simulation, and the wave impedance model of the coil is established based on ATP-EMTP. The low-voltage square wave pulse signal is injected at the winding head to detect the characteristic curve of reflected wave when inter-turn short circuit fault occurs. The variation law of generalized fractal dimension of reflection wave characteristic curve with short circuit position is analyzed. The short-circuit position is evaluated based on BP neural network, and the evaluation accuracy is 100 %, indicating that this method is feasible.